Pengaruh Literasi Keuangan, Penggunaan Informasi Keuangan Dan Pengetahuan Akuntansi Pada Kinerja UMKM di Kota Semarang - Rokhimah, Zulaika Putri; Sari, Titi Purbo; Widodo, Agus (Politeknik Raflesia Press, 2024)
This research aims to determine the influence of financial literacy, use of financial information and accounting knowledge on the performance of Micro, Small and Medium Enterprises (MSMEs) in the Semarang city area. Financial literacy is the use of financial information and accounting knowledge which is an important factor in improving the performance and productivity of MSMEs. By understanding good financial literacy, MSME players are expected to be able to make the right financial decisions so as to improve the financial performance of MSMEs. Using financial information properly will help you find out how your business is developing. Having knowledge related to accounting can help and consider the financial conditions of the business being run. The method used in this research is quantitative. Data collection was carried out by using questionnaires to MSME actors in the city of Semarang directly or using Google Form via a link so that it could reach the entire city of Semarang. Instrument testing uses SPSS. The results obtained are that financial literacy influences the performance of MSMEs, while the use of financial information and accounting knowledge does not influence the performance of MSMEs.